Successful treatment with convalescent plasma in Covid-19 disease in relaps/refractory multiple myeloma (Annals of Medical Research, 2021)
The Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus detected in the Wuhan Province of the People's Republic of China caused a pandemic in a very short time all over the world. Convalescent plasma (CP) therapy is a passive antibody therapy that has been shown to be effective in epidemic periods. CP therapy has been of interest in the treatment of infection with no vaccine or specific treatment, such as the Sars-CoV-2 infection that causes COVID-19. We aimed to report our CP experience in Sars-Cov-2 infection in our relapsed / refractory Multiple myeloma (MM) patient.